IL-15 transpresentation promotes both human T-cell reconstitution and T-cell–dependent antibody responses in vivo - Huntington, Nicholas D. (National Academy of Sciences, 2011)
Cytokine immunotherapies targeting T lymphocytes are attractive clinical interventions against viruses and tumors. In the mouse, the homeostasis of memory α/β CD8(+) T cells and natural killer (NK) cells is significantly improved with increased IL-15 bioavailability. In contrast, the role of “transpresented” IL-15 on human T-cell development and homeostasis in vivo is unknown. We found that both CD8 and CD4 T cells in human immune system (HIS) mice are highly sensitive to transpresented IL-15 in vivo, with both naïve (CD62L(+)CD45RA(+)) and memory phenotype (CD62L(−)CD45RO(+)) subsets being significantly increased following IL-15 “boosting.” The unexpected global improvement in human T-cell homeostasis involved enhanced proliferation and survival of both naïve and memory phenotype peripheral T cells, which potentiated B-cell responses by increasing the frequency of antigen-specific responses following immunization. Transpresented IL-15 did not modify T-cell activation patterns or alter the global T-cell receptor (TCR) repertoire diversity. Our results indicate an unexpected effect of IL-15 on human T cells in vivo, in particular on CD4(+) T cells. As IL-15 promotes human peripheral T-cell homeostasis and increases the frequency of neutralizing antibody responses in HIS mice, IL-15 immunotherapy could be envisaged as a unique approach to improve vaccine responses in the clinical setting.